Myanmar Economic Monitor, December 2016 : Anchoring Economic Expectations - World Bank Group (World Bank, Washington, DC, 2017)
The Myanmar Economic Monitor (MEM) periodically takes stock of economic developments anddiscusses economic prospects and policy priorities in Myanmar. The MEM draws on available datareported by the Government of Myanmar and additional information collected as part of the WorldBank Group’s regular economic monitoring and policy dialogue. The government has carefully navigated a difficult economic and security environment in its first six months in office. In early April 2016, the economy was still recovering from a flood induced supply shock, which, together with low commodity prices, contributed to widening current account and fiscal deficits. In response the government has taken steps to try and maintain fiscal prudence, which have helped ease pressure on monetary growth and import demand.